Self-care of Consumption of Psychotropic Substances in Nursing Student - Monserrate Macias Alvia, Aida; Rincon Rios, Tibisay; Olmedo Zambrano Santos, Roberth; Vite Solorzano, Franklin (International Journal of Psychosocial Rehabilitation, 2020)
The use of psychotropic substances has become a global public health problem. Ecuador does not escape this reality, because students of health careers, knowing the harmful consequences of the consumption of these substances, have these practices without any qualms. The objective of the research was to determine the importance of self-care in preventing the use of psychotropic substances in nursing students at Southern Manabí State University. The research was a descriptive-analytic longitudinal cohort. As theoretical methods, analysis-synthesis, logical and inductive-deductive history, and as an empirical method, the survey was used, aimed at students. It was possible to determine that these students regularly consume tobacco and alcohol. Also, it was discovered that there are students who use drugs illicitly.